A absorção de ferro pela cana de açúcar, Co 419, em função da idade - Bittencourt, V. C. de; Catani, R .A.; Pellegrino, D.; Glória, N. A. da (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1963)
This paper describes the results obtained from the determination of iron in sugar cane according to the age of the plant, in the soil and climate conditions of the state of S. Paulo, Brazil. The iron was determined by 1-10- phenanthroline method, in samples cut monthly from 7th to 15th month from an experiment consisted de 3 plots fertilized with amonium sulfate, superphosphate and potassium cloride. The concentration of iron in the stalks and in the leaves varies according to the age of the plant. A ton of fresh stalks 15 months old contains 78,71 g of iron.